Functionalized Microgel Rods Interlinked into Soft Macroporous Structures for 3D Cell Culture. Issue 10 (14th January 2022) - Rommel, Dirk; Mork, Matthias; Vedaraman, Sitara; Bastard, Céline; Guerzoni, Luis P. B.; Kittel, Yonca; Vinokur, Rostislav; Born, Nikolai; Haraszti, Tamás; De Laporte, Laura
Abstract: In this work, a two component microgel assembly using soft anisometric microgels that interlink to create a 3D macroporous construct for cell growth is reported. Reactive microgel rods with variable aspect ratio are produced via microfluidics in a continuous plug‐flow on‐chip gelation method by photoinitiated free‐radical polymerization of star‐polyethylene glycol‐acrylate with glycidyl methacrylate or 2‐aminoethyl methacrylate comonomers. The resulting complementary epoxy‐ and amine‐functionalized microgels assemble and interlink with each other via a ring opening reaction, resulting in macroporous constructs with pores up to several hundreds of micrometers. The level of crosslinking depends on the functionalization degree of the microgels, which also affects the stiffness and cell adhesiveness of the microgels when modified with the cell‐adhesive GRGDS‐PC peptide. Therefore, 3D spreading and growth of cells inside the macroporous structure is influenced not only by the presence of macropores but also by the mechanical and biochemical properties of the individual microgels. Abstract : Two types of microgel rods produced in microfluidics bear active groups enable quick and stable rod interlinking when they come in contact in the aqueous phase. This way, macroporous scaffolds with micro‐ to millimeter‐scale pores are formed that support 3D‐cell culture of human fibroblasts and endothelial cells. Cells attach, spread, and grow, filling the macropores, building biological‐like tissue material.